Rocket and Two Dimensional Immunoelectrophoresis in Diagnosis of Caprine Brucellosis - Davood MEHRABANI; Zahra GHOLAMI; Jamshid KOHANTEB; Masood SEPEHRIMANESH; SeyedMohammad Hossein-HOSSEINI (Tehran University of Medical Sciences, 2015)
Background: Brucellosis is a major bacterial zoonosis of global importance with the causative organisms of Gram-negative facultative intracellular pathogens. The aims of this study were to standardize two immunoelectrophoretic techniques, rocket and cross immunoelectrophoresis, and compare their results with other conventional serodiagnostic tests. Methods: Sera from 15 sheep, without any history of brucellosis vaccination, infected with Brucella melitensis M16 sub-cutaneously, were employed in a comparison of culture, precipitating, and immunoelectrophoretic tests. A 125 days serologic follow-up was performed after the infection was started. As a reference, these tests also done in the five healthy sheep. Results: The results obtained with the rocket immunoelectrophoresis test correlated very well with those of the cross immunoelectrophoresis, whereas results of other tests such as culture, Rose Bengal, standard tube agglutination and 2-mercaptoethanol seruagglutination tests were inferior. Conclusion: As agglutination test shows cross reaction and a prozone phenomenon, and in blood culture, the bacte-ria is not always detectable, so they are time consuming rocket and cross immunoelectrophoresis are recommended because their results can be obtained in a shorter time.